ResDE Two-Component Regulatory System Mediates Oxygen Limitation-Induced Biofilm Formation by Bacillus amyloliquefaciens SQR9 - Zhou, Xuan (Appl Environ Microbiol, 2018)
Efficient biofilm formation and root colonization capabilities facilitate the ability of beneficial plant rhizobacteria to promote plant growth and antagonize soilborne pathogens. Biofilm formation by plant-beneficial Bacillus strains is triggered by environmental cues, including oxygen deficiency, but the pathways that sense these environmental signals and regulate biofilm formation have not been thoroughly elucidated. In this study, we showed that the ResDE two-component regulatory system in the plant growth-promoting rhizobacterium Bacillus amyloliquefaciens strain SQR9 senses the oxygen deficiency signal and regulates biofilm formation. ResE is activated by sensing the oxygen limitation-induced reduction of the NAD(+)/NADH pool through its PAS domain, stimulating its kinase activity, and resulting in the transfer of a phosphoryl group to ResD. The phosphorylated ResD directly binds to the promoter regions of the qoxABCD and ctaCDEF operons to improve the biosynthesis of terminal oxidases, which can interact with KinB to activate biofilm formation. These results not only revealed the novel regulatory function of the ResDE two-component system but also contributed to the understanding of the complicated regulatory network governing Bacillus biofilm formation. This research may help to enhance the root colonization and the plant-beneficial efficiency of SQR9 and other Bacillus rhizobacteria used in agriculture. IMPORTANCE Bacillus spp. are widely used as bioinoculants for plant growth promotion and disease suppression. The exertion of their plant-beneficial functions is largely dependent on their root colonization, which is closely related to their biofilm formation capabilities. On the other hand, Bacillus is the model bacterium for biofilm study, and the process and molecular network of biofilm formation are well characterized (B. Mielich-Süss and D. Lopez, Environ Microbiol 17:555–565, 2015, https://doi.org/10.1111/1462-2920.12527; L. S. Cairns, L. Hobley, and N. R. Stanley-Wall, Mol Microbiol 93:587–598, 2014, https://doi.org/10.1111/mmi.12697; H. Vlamakis, C. Aguilar, R. Losick, and R. Kolter, Genes Dev 22:945–953, 2008, https://doi.org/10.1101/gad.1645008; S. S. Branda, A. Vik, L. Friedman, and R. Kolter, Trends Microbiol 13:20–26, 2005, https://doi.org/10.1016/j.tim.2004.11.006; C. Aguilar, H. Vlamakis, R. Losick, and R. Kolter, Curr Opin Microbiol 10:638–643, 2007, https://doi.org/10.1016/j.mib.2007.09.006; S. S. Branda, J. E. González-Pastor, S. Ben-Yehuda, R. Losick, and R. Kolter, Proc Natl Acad Sci U S A 98:11621–11626, 2001, https://doi.org/10.1073/pnas.191384198). However, the identification and sensing of environmental signals triggering Bacillus biofilm formation need further research. Here, we report that the oxygen deficiency signal inducing Bacillus biofilm formation is sensed by the ResDE two-component regulatory system. Our results not only revealed the novel regulatory function of the ResDE two-component regulatory system but also identified the sensing system of a biofilm-triggering signal. This knowledge can help to enhance the biofilm formation and root colonization of plant-beneficial Bacillus strains and also provide new insights of bacterial biofilm formation regulation.